Optimalisasi Keuntungan Atas Produk-Produk Pada Usaha Sanggar Ukir Kayu di Tenggarong (Penerapan Linear Programming Dengan Metode Simpleks) - Devi Putri Aprilia Nur; Raudatul Adawiyah; Kartina Eka Ningsih (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2022)
Abstract :The main objective of this research is to find out if any kind of timber production in Wood Carving Studio has reached the maximum profit. A series of observations carried out on the object of research, namely Wood Carving Studio Effort in Tenggarong in which Companies will get the maximum benefit from the product combination product i.e. 2 Ventilation (X 2) with the number of optimal production by as much as 100 units and Nameplate (X 3) and the number of optimal production by as much as 75 units. Maximum benefits will achieved Rp 16,525,000,-. For the cost of ulin wood or slack 1 (S1) and the cost of paint or slack 3 (S3) each still costs as much as Rp meyisakan,-2.5 million and Rp 75,000,-this indicates that companies can save costs on slack slack 1 and 3 respectively as much as Rp 2.5 million, -and Idr 75,000,-or can aggregate to Rp 2,575,000,-for 3 months. Unlike for products that have the status of non basic or value of 0 (zero) this means that other products better not manufactured by the company because it does not generate the maximum profits. Then the hypothesis has been put forward previously stating